Ra-COMPACTNESS ON BITOPOLOGICAL SPACES - Majeed, Rasha Naser (Al-Nahrain Journal of Science, 2010)
In this paper we define a new type of open sets in bitopological space which we called Ra-open sets, which leads to define a new type of compactness on bitopological spaces called "Ra-compactness" and we study the properties of this spaces, also we define the continuousfunctions between these spaces